Improving Accuracy of Malaria Diagnosis in Underserved Rural and Remote Endemic Areas of Sub-Saharan Africa: A Call to Develop Multiplexing Rapid Diagnostic Tests - Rasheed O. Makanjuola; Andrew W. Taylor-Robinson (Scientifica)
Clinical infection with malaria, caused by parasites of the genus Plasmodium, is considered a serious medical condition with the potential to become a life-threatening emergency. This is especially relevant to low-income countries in tropical and subtropical regions of the world where high rates of malaria-related morbidity and mortality are recorded. As a means to combat this major global public health threat, rapid and effective diagnosis remains the frontline action to initiate a timely and appropriate medical intervention. From all the approaches to parasite detection, rapid diagnostic tests, so-called RDTs, are the easiest to use and most cost-effective. However, some of the limitations inherent in this methodology could hinder effective patient treatment. A primary drawback is that the vast majority of commercially available RDTs detect only one of the five species of human malaria, P. falciparum. While this is the main cause of infection in many areas, it excludes the possibility of infection with another parasite (P. vivax, P. ovale, P. malariae, and P. knowlesi) or of mixed infections containing different species. Hence, a diagnosis of non-P. falciparum malaria is missed. In turn, in resource-constrained settings where optimal microscopy is not available, a misdiagnosis of bacterial infection based on signs and symptoms alone often results in an inappropriate prescription of antibiotics. Here, we discuss how effective diagnosis of malaria and indiscriminate use of antibiotics in sub-Saharan Africa, a hot spot for P. falciparum transmission, may both be addressed by the development of innovative multiplexing RDTs that detect two or more species of Plasmodium.